(untitled) (Bangladesh Journal of Medical Science, 2016)
Insulin neuropathy is a rare adverse effect of insulin therapy in patients with long-term uncontrolled hyperglycemia. Neuropathic pain appears after the correction of blood glucose level. A 34 years old woman with severe neuropathic pain appeared immediately after the beginning of insulin therapy and could not be responded to neuropathic pain relief drugs is reported. Insulin treatment may cause severe neuropathic pain that cannot be result with neuropathic pain relief drugs. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.303-304